Faktor Penyebab Stunting Pada Anak: Tinjauan Literatur - Yanti, Nova Dwi; Betriana, Feni; Kartika, Imelda Rahmayunia (Universitas Fort De Kock Bukittinggi, 2020)
Background: Stunting is defined as a short or very short body state caused by various factors. Objective: This article aims to review factors causing stunting, including mother`s knowledge and parenting style, nutrition intake, low birth weight (LBW), and family`s financial status. Method: This literature review was conducted through searching relevant evidences from electronic database (Google scholar) using the following keywords: